Traction Optimization Control of CRH2G Anti-cold EMUs for Traction Power Improvement - YANG Liangchong (机车电传动)
In order to improve the running speed on 20‰ ramps of CRH2G anti-cold EMUs, shorten the travel time, and also satisfy the higher speed and better vehicles reliability under the environment of high altitude, high temperature, 20‰ ramps of Lanzhou-Urumchi high-speed railway, a traction optimization control strategy of CRH2G by optimizing the VF output characteristics of the motor and improving the harmonic performance of the motor current for the traction power improvement was proposed. Both the ground test results and the line test data showed that the proposed optimization control method was effective.